MENELUSURI NILAI-NILAI RELIGIUSITAS NOVEL “HAFALAN SHALAT DELISA” KARYA TERE LIYE - Hani Greisilavia Andaresta; Dimas Oky Kurnianto; Pardiyatmoko (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
Literature, as an artistic medium, goes beyond narrative and plays a role in creative expression. The novel, a manifestation of prose, serves as a narrative vehicle that reveals the intricacies of life and the characters involved in it from beginning to end. There is a deep connection between literature and religiosity. One of the novels that has a rich religious theme and values is